2018
DOI: 10.1002/cam4.1927
|View full text |Cite
|
Sign up to set email alerts
|

Application of risk factors for venous thromboembolism in patients with multiple myeloma starting chemotherapy, a real‐world evaluation

Abstract: IntroductionWithin the first year of diagnosis, up to 1 in 3 multiple myeloma (MM) patients will experience a venous thromboembolism (VTE). The International Myeloma Working Group (IMWG) has thromboprophylaxis guidelines that stratify patients into low or high risk for thrombosis and subsequently recommend thromboprophylaxis, but it is unknown if these recommendations are being followed or if they are effective. The purpose of this study was to assess efficacy of the IMWG guidelines and investigate other poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…There was no association between the initial risk stratification and the mode of thromboprophylaxis of use. Therefore, it was demonstrated that guideline concordance in terms of either aspirin (ASA) or LMWH was lower than expected [22].…”
Section: Treatment-related Risk Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…There was no association between the initial risk stratification and the mode of thromboprophylaxis of use. Therefore, it was demonstrated that guideline concordance in terms of either aspirin (ASA) or LMWH was lower than expected [22].…”
Section: Treatment-related Risk Factorsmentioning
confidence: 96%
“…Body mass index >25, Age >75, Personal or family history of VTE, Central venous catheter, Acute infection or Hospitalization, Blood clotting disorders or Thrombophilia, Immobility with performance status of >1, Comorbidities (liver, renal impairment, chronic obstructive pulmonary disorder, diabetes mellitus, chronic inflammatory bowel disease), Race (Caucasian is a risk factor) These guidelines have been available since 2014; however, data from clinical trials demonstrate that the rates of residual VTE remain high [22][23][24]. Therefore, it is safe to conclude that the current risk stratification is suboptimal and fails to fully capture and distinguish between low, intermediate, and high-risk MM patients for VTE.…”
Section: Treatment-related Risk Factors: Assign Points As Seen Belowmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, both the accuracy of the IMWG/NCCN model for predicting the development of VTE, as well as its use outside of clinical trials, have been poor. 18,19 Furthermore, recent attempts at validating the IMWG/NCCN model in 2 large cohorts-SEER-Medicare and Veterans Administration Healthcare System-demonstrated that the model's discriminatory performance as measured by Harrell's c-statistic (measured from 0.5-1.0 as the best "fit" of a propensity score model assessing the risk) was suboptimal in both groups, at 0.52 and 0.55, respectively. 16,17 On the other hand, both the SAVED and the IMPEDE VTE models performed slightly better, with external validations at 0.60 and 0.64, respectively.…”
Section: Best Vte Risk Assessment Models In MMmentioning
confidence: 99%
“…A real-world study of VTE prophylaxis in NDMM demonstrated that only 19% of patients received appropriate prophylaxis per the IMWG guidelines. 18 A recent analysis of the GRIFFIN trial similarly showed that only 60% of patients treated with DRVd and 67% of those treated with RVd were receiving antithrombotic prophylaxis at the time of their VTE (ASA in 40% and 60% of patients, and LMWH in 10% and 7% of patients, respectively), suggesting that use of antithrombotic prophylaxis remains suboptimal even among mostly academic centers. 30 Finally, prospective validation of the SAVED and IMPEDE-VTE models is needed in order to determine the ideal thromboprophylaxis strategy based on baseline risk stratification and treatment regimen, ideally also incorporating biomarkers predictive of VTE risk.…”
Section: Best Vte Risk Assessment Models In MMmentioning
confidence: 99%